ANALISIS RANTAI PASOK GURITA (Octopus sp) PADA CV. OCTOPUS SHOP DI BANDA ACEH - Della Kartika; Agus Naufal; Faisal Syahputra (Lembaga Riset dan Inovasi Kreyat Center, 2025)
The city of Banda Aceh holds promising potential in the capture fisheries sector due to the abundance of marine resources and the high volume of fishery commodity exports, which contribute to regional income growth and attract investor interest. This study aims to analyze the octopus (Octopus sp) supply chain at CV. Octopus Shop in Banda Aceh, focusing on the supplying areas and the factors that influence production. The research employs a quantitative approach through observation, interviews, and documentation. The findings indicate that there are eight octopus-supplying areas, with Pulau Aceh being the largest supplier (7,629 kg or 31%) and Krueng Raya the smallest (889 kg or 4%). CV. Octopus Shop applies a supply chain system with one upstream channel and three downstream channels, namely fisher–supplier–collector/distributor (CV. Octopus Shop)–PT Toba Surimi Industries–local markets–restaurants. Variations in production among regions are influenced by factors such as seasons, environmental conditions, differences in fishing techniques and equipment, human activities such as overfishing, marine pollution, coastal development, and competition among fishers. This research contributes to the development of a more and sustaineble octopus supply chain strategy to enhance the economic value for fishers and business actors in Banda Aceh.